Genetic Diversity and Host Specificity Varies across Three Genera of Blood Parasites in Ducks of the Pacific Americas Flyway - Reeves, Andrew B. (PLoS One, 2015)
Birds of the order Anseriformes, commonly referred to as waterfowl, are frequently infected by Haemosporidia of the genera Haemoproteus, Plasmodium, and Leucocytozoon via dipteran vectors. We analyzed nucleotide sequences of the Cytochrome b (Cytb) gene from parasites of these genera detected in six species of ducks from Alaska and California, USA to characterize the genetic diversity of Haemosporidia infecting waterfowl at two ends of the Pacific Americas Flyway. In addition, parasite Cytb sequences were compared to those available on a public database to investigate specificity of genetic lineages to hosts of the order Anseriformes. Haplotype and nucleotide diversity of Haemoproteus Cytb sequences was lower than was detected for Plasmodium and Leucocytozoon parasites. Although waterfowl are presumed to be infected by only a single species of Leucocytozoon, L. simondi, diversity indices were highest for haplotypes from this genus and sequences formed five distinct clades separated by genetic distances of 4.9%–7.6%, suggesting potential cryptic speciation. All Haemoproteus and Leucocytozoon haplotypes derived from waterfowl samples formed monophyletic clades in phylogenetic analyses and were unique to the order Anseriformes with few exceptions. In contrast, waterfowl-origin Plasmodium haplotypes were identical or closely related to lineages found in other avian orders. Our results suggest a more generalist strategy for Plasmodium parasites infecting North American waterfowl as compared to those of the genera Haemoproteus and Leucocytozoon.